The impact of COVID-19 lockdown on the noise pollution: case study in the city of Skopje - Domazetovska, Simona; Anachkova, Maja; Gavriloski, Viktor; Sokolikj, Ankica; Stojkovska, Sandra (Institute of Noise Control Engineering (INCE), 2021)
The lockdown that the city of Skopje has suffered during the months of April to June 2020 in order to control the spread of COVID-19 has significantly changed the acoustic environment in the urban parts of the city. The absence of vehicles, people on the streets and closed restaurants has led to a noise reduction captured by the low-cost wireless sensor network in the City of Skopje. The analysis carried out in this paper show reduction in noise pollution strongly correlated with the population's activity and behavior to the new circumstances. Overall, the sound pressure levels vary around 65 dB; however, some extreme decrease can be noticed, especially during the quarantine weekends. Also, the noise levels were compared between the same time periods during the year of 2019 and 2020, where it can be perceived reduction in the sound level for 36,5% for the day-evening-night noise level indicator (L). Significant variations occur for the indicators L, L, and L, especially during the lockdown weekends.